2016
DOI: 10.1017/ice.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Infection Reduction in Outpatient Hemodialysis Centers Participating in a Collaborative Bloodstream Infection Prevention Effort

Abstract: Among dialysis facilities participating in a bloodstream infection (BSI) prevention collaborative, access-related BSI incidence rate improvements observed immediately following implementation of a bundle of BSI prevention interventions were sustained for up to 4 years. Overall, BSI incidence remained unchanged from baseline in the current analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Whereas the bloodstream infection rate reported by the Centers for Disease Control and Prevention (CDC) for 2014 in patients with an arteriovenous fistula was 0.26 per 100 patient-months, in those with a catheter, it was 2.16 (4,5). Reports have noted considerable variability between facilities and infection control interventions can reduce facility bloodstream infection rates (6)(7)(8)(9)(10). These data, and the higher mortality rate of patients with a catheter (3,(11)(12)(13), have prompted the Centers for Medicare and Medicaid Services (CMS) to consider both the proportion of patients with a catheter and the bloodstream infection rates in hemodialysis facilities as quality measures in the ESKD Quality Incentive Program (QIP) (14).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the bloodstream infection rate reported by the Centers for Disease Control and Prevention (CDC) for 2014 in patients with an arteriovenous fistula was 0.26 per 100 patient-months, in those with a catheter, it was 2.16 (4,5). Reports have noted considerable variability between facilities and infection control interventions can reduce facility bloodstream infection rates (6)(7)(8)(9)(10). These data, and the higher mortality rate of patients with a catheter (3,(11)(12)(13), have prompted the Centers for Medicare and Medicaid Services (CMS) to consider both the proportion of patients with a catheter and the bloodstream infection rates in hemodialysis facilities as quality measures in the ESKD Quality Incentive Program (QIP) (14).…”
Section: Introductionmentioning
confidence: 99%
“…The data in this report also demonstrated individual facility-level effects. In 2016, a follow-up study of the same 17 centers confirmed the initial reduction in access-related BSIs, and found that lowered rates were sustained in these centers for at least 4 years after the interventions were implemented (13). The greatest reductions in infection rate were observed among patients with CVCs and an estimated 286 access-related BSIs were prevented (among 46,351 patient-months) during the 48-month intervention period assessed.…”
Section: Activities Outcomes and Products Of The Collaborativementioning
confidence: 86%
“…Several reports that emerged from the Collaborative have described its effect (8,12,13). A single Collaborative participant facility reported a reduction in access-related BSI rates from 2.04 per 100 patient-months preintervention to 0.75 per 100 patient-months after implementing Collaborative interventions, and a further reduction to 0.24 per 100 patient-months after adding a behavioral change intervention (12).…”
Section: Activities Outcomes and Products Of The Collaborativementioning
confidence: 99%
“…186 In a follow-up study, the reduction in access-related BSI rates was sustained for 4 years after the initial intervention implementation. 187 The over-representation of hospital-based centers and lack of a control group limit generalization of these data. However, the ongoing simplification of audit tools for ease of reporting with the use of information technology-as used in this studyprecludes the need of infection control professionals on site, and leaves little justification to not recommend implementation of audits.…”
Section: External Cleaningmentioning
confidence: 99%